GOVERNMENT SPENDING ON HIGHER EDUCATION IN INDIA: AN ECONOMIC PERSPECTIVE - Dr. V. Siva Elango (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper attempts to estimate the contribution of public expenditure on education to economic growth by using the central government expenditure on education. It has been observed that the public expenditure on higher education is positively associated with increasing gross enrollment ratio and growing higher educational institutions in India. The cumulative growth rate of public expenditure on higher education is 16.18 per cent per annum and GER in higher education growing at 5.75 per cent in every year during the 1991 to 2022. This work suggests to the government that focus must be given on small towns, rural areas, remote villages and backward regions where GER is very low compare to the urban area. Government should allow ability to pay fee policy after studying the unit cost of education at different levels, programmes, quality and scale of higher education. An essential aspect of the fee policy should be discrimination in favour of poor and full cost recovery from the rich.